2014
DOI: 10.1111/cmi.12340
|View full text |Cite
|
Sign up to set email alerts
|

Lipid interactions during virus entry and infection

Abstract: SummaryFor entry and infection viruses have developed numerous strategies to subjugate indispensable cellular factors and functions. Host cell lipids and cellular lipid synthesis machinery are no exception. Not only do viruses exploit existing lipid signalling and modifications for virus entry and trafficking, they also reprogram lipid synthesis, metabolism, and compartmentalization for assembly and egress. Here we review these various concepts and highlight recent progress in understanding viral interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(106 citation statements)
references
References 101 publications
3
103
0
Order By: Relevance
“…However, Laliberte and Moss demonstrated that phospholipids other than PS could also reconstitute MV infectivity (23). To date, there is no evidence that any particular PS receptor is required for vaccinia MV entry (24)(25)(26).…”
Section: Vaccinia Mature Virions Of the Wr Strain Enter Hela Cells Thmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Laliberte and Moss demonstrated that phospholipids other than PS could also reconstitute MV infectivity (23). To date, there is no evidence that any particular PS receptor is required for vaccinia MV entry (24)(25)(26).…”
Section: Vaccinia Mature Virions Of the Wr Strain Enter Hela Cells Thmentioning
confidence: 99%
“…However, Laliberte and Moss demonstrated that phospholipids other than PS could also reconstitute MV infectivity (23). To date, there is no evidence that any particular PS receptor is required for vaccinia MV entry (24)(25)(26).Following internalization into cells, the vaccinia virus MVcontaining vesicles are internalized into CD98-positive and phosphatidylinositol 3-phosphate (PI3P)-positive macropinosomes and subsequently fused with Rab5-positive early endosomes (19). However, little is known about the process of sorting the MVcontaining vesicles in cells prior to membrane fusion.…”
mentioning
confidence: 99%
“…KHV replication was confirmed by transmission electron microscopy analysis, demonstrating viral particles inside the nucleus of CCB and KoK cells. KoK, but not CCB cells, produced large lipid droplets (data not shown), which might be a sign of accelerated lipid metabolism upon virus replication (Mazzon & Mercer, ). Electron microscopy analysis of ASK and Fr994 revealed replication events, that are typical for members of the orthomyxovirus family, for example, influenza viruses (Nayak, Hui, & Barman, ).…”
Section: Discussionmentioning
confidence: 87%
“…Many viruses are highly dependent on host lipid metabolism for replication [27]. Lipid metabolism is therefore considered as a prime target for BSAA.…”
Section: Modulators Of Lipid Metabolismmentioning
confidence: 99%